ANALISIS KEWENANGAN LEMBAGA NEGARA DI BAWAH KEKUASAAN EKSEKUTIF SEBAGAI PELAKSANA UNDANG-UNDANG - Putra, Nandaswara Shandi; Samhudi, Gamalel Rifqi (LPPM STIH Awang Long, 2025)
In Indonesia, the discussion on independent state institutions has been growing rapidly since the reform era. One issue that continues to be discussed to this day is the extent to which the law guarantees the independence of an institution, in this case specifically the Corruption Eradication Commission (hereinafter KPK). However, after the amendment of the KPK Law, the existence of this institution has caused debate in the community. From one point of view, the KPK is explicitly stated as part of the executive power, but from another point of view it is also emphasized that in carrying out its duties and authorities, the KPK remains independent and is not under the influence of any power. The purpose of this study is to determine and analyze the independence of state institutions under executive power, and to determine and analyze the impact of the Corruption Eradication Commission being a state institution under executive power. This research is expected to contribute to the development of legal science, especially in constitutional law. Practically, the results of this research are also expected to be a reference and input for parties in the field of law, as well as a medium to expand knowledge. This research uses a normative juridical approach, which is a legal research method that relies on the analysis of available literature. The specification of this research is descriptive analytical, namely a comprehensive description of the positive legal conditions prevailing in society. The data collection technique used is literature study. The existence of a supervisory board in the Corruption Eradication Commission is based on a number of important reasons, namely the Super Body Principle, (because it has much broader authority compared to the Police and the Attorney General's Office), then Abuse of Power.